Low Dose Morphine Enhances Morphine Antinociception Effectsin the Animals Pretreated with Selective and Non-Selective Phosphodiestrase Inhibitors: Effects of phosphodiesterase inhibitors on morphine antinociception - Mohammad Hassan Karimfar; Shervin Gholizadeh; Amir Peyman Hajrasouliha; Kaveh Tabrizian; Kian Azami; Mohammad Abdollahi; Mohammad Sharifzadeh; Abdol Hossain Miri (Iranian Journal of Pharmaceutical Sciences, 2009)
In this study, we investigated the interactive effects of intraperitoneal (i.p.)injections of three different phosphodiesterase inhibitors (PDEIs) on morphine-induced analgesia in mice using tail-flick method. Subcutaneous administration of morphine (1, 3 and 6 mg/kg) caused significant antinociceptive effects in a dose dependent manner. Administration of pentoxifylline (12.5, 25, 50 and 100 mg/kg,i.p.), milrinone (3 and 4.5 mg/kg, i.p.) and theophylline (25, 50 and 100 mg/kg, i.p.)as selective and non-seletive phosphodiesterase in hibitors in duced analgesia inmice. We also examined the antinociceptive effects of these three PDEIs incombination with non-effective dose of morphine (1 mg/kg). These combinations increased analgesia effects compared to the either morphine or respective phospho-diestrase inhibitor groups significantly. Our findings strongly suggest that PDEIs can induce analgesia and potentiate morphine antinociception effect via possible interactions on the same molecular or biochemical pathways.